ALGORITHM FOR OPTIMIZING THE COMBUSTION PROCESS OF ASSOCIATED PETROLEUM GAS IN THERMAL POWER PLANTS, TAKING INTO ACCOUNT THE VARIABILITY OF ITS COMPOSITION - V. M. Larionov; E. R. Saifullin; S. A. Nazarychev; A. O. Malahov; Y. V. Vankov (Известия высших учебных заведений: Проблемы энергетики)
Problems of natural resources rational using, energy efficiency and energy saving are topical at present. As part of this problem is actual task of rational and efficient use of associated petroleum gas. The composition of associated petroleum gas due to the nature of its production variable over time. These changes lead to the violation of the combustion optimal mode in thermal power plants. This article presents the algorithm of combustion optimization of hydrocarbon fuels variable composition, in particular of associated petroleum gas. There were developed the algorithms: the determination of initial ratio "fuel-air" in thermal power plants and to bring this ratio to the optimum; optimization of the combustion process during change of the specific heat of combustion. The algorithms are based on registration of change coolant temperature at the outlet of thermal power plant.